До історії колонізації Нижнього Побужжя - Крижицький, С.Д. (Археологія, 1989)
У статті пропонуються археологічні критерії класифікації поселень Нижнього Побужжя VI ст. до н. е., на основі яких зроблені висновки про характер грецької колонізації регіону. В статье предлагаются критерии классификации поселений по археологическим данным (категория планировки поселения; характер организации пространства между отдельными домовладениями; принципы формирования кварталов; состав градообразующих структур; характер объемно-планировочных типов домов). На основании анализа поселений по этим критериям возможны следующие выводы: нижнебугские поселения являются не случайным типом поселений этапа колонизации, специфика которых была обусловлена отсутствием государственности, а также однородностью социального состава переселенцев — малозажиточных сельских жителей; в колонизации VI в. до н. э. в Северном Причерноморье выделяются две основные линии: организованная целенаправленная колонизация (Березанское поселение) и стихийная аграрная, охватившая территории, которые прибывшие ранее поселенцы в силу своей малочисленности не могли освоить. Эта вторая линия колонизации создала условия и предпосылки для возникновения Ольвийского государства. В терминологическом отношении города и поселения Ольвийского государства в последней четверти VI — первой четверти V вв. до н. э. можно определить так: Ольвия — полис (в значении крупный город); Березанское поселение — полихнион (в значении небольшой городок); агломерация — коме (неукрепленная деревня); поселение, состоящее из одного — нескольких ойкосов,— комион (деревушка). Settlement classification criteria based on archaeological data are suggested (a category of the settlement lay-out, a mode of the space organization between particular householders; principles for district planning; composition of town-forming structures; volume- lay-out types of houses). Analysis of these settlements according to above criteria permits the following conclusions: the low Bug area settlements are not accidental settlements characteristic of the colonization stage; their specificity was a result of the absence of the political system and homogeneity of the social composition of settlers, not prosperous rural dwellers. Colonization in the North Black Sea area in the 6th century B.C.
proceeded in two main lines: organized purposeful colonization (Berezanian settlement) and spontaneous agrarian colonization which embraced the territories which could not De developed by settlers who had come there previously as they were very scanty in number. That second line of colonization created conditions and premises for the Olbian state to appear. In the terminological aspect towns and settlements of the Olbian state in me second quarter of the 6th cent, and first quarter of the 5th cent. B.C. may be determined as follows: Olbia — polis (in the meaning of large city); Berezanian settlement— polychnion (in the meaning of small town); aglomeration — kome (unfortified village); settlement consisting of one or some oikses — komion (small village).